Optimizing Stormwater Treatment Practices A Handbook of Assessment and Maintenance - Erickson, Andrew J.; Weiss, Peter T.; Gulliver, John S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Optimizing Stormwater Treatment Practices: A Handbook of Assessment and Maintenance provides the information necessary for developing and operating an effective maintenance program for stormwater treatment. The book offers instructions on how to measure the level of performance of stormwater treatment practices directly and bases proposed maintenance schedules on actual performance and historical maintenance efforts and costs. The inspection methods, which are proven in the field and have been implemented successfully, are necessary as regulatory agencies are demanding evaluations of the performance of stormwater treatment practices. The authors have developed a three-tiered approach that offers readers a standard protocol for how to determine the effectiveness of stormwater treatment practices currently in place. This book also: Provides a standard protocol for how to determine the effectiveness of stormwater treatment practices Assists readers with identifying which assessment techniques to use for stormwater treatment while also providing instructions on implementation methods Contains a substantial number of examples and case studies to illustrate the use of the methods discussed in the book Optimizing Stormwater Treatment Practices: A Handbook of Assessment and Maintenance is an ideal reference and handbook for stormwater professionals.  .
Introduction -- Impacts and Composition of Urban Stormwater -- Stormwater Treatment Processes -- Stormwater Treatment Practices -- Visual Inspection of Stormwater Treatment Practices -- Capacity Testing of Stormwater Treatment Practices -- Synthetic Runoff Testing of Stormwater Treatment Practices -- Monitoring of Stormwater Treatment Practices -- Water Budget Measurement -- Water Sampling Methods -- Analysis of Water and Soils -- Data Analysis -- Maintenance of Stormwater Treatment Practices.
Keywords: Civil engineering; Water quality; Water pollution; Environmental monitoring; Civil Engineering; Water Quality/Water Pollution; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Monitoring/Environmental Analysis